Dirty Words: Discursive Generativity & Social Stigmata, Murder & Capital - Selsky, Dave (MacEwan University Student eJournal, 2016)
A structural analysis of the discursive approach in Kevin Dutton's book, The Wisdom of Psychopaths, with Žižek's concept of violence, questioning the validity of Dutton's thesis.